Gel formulated with Bryophyllum pinnatum leaf extract promotes skin wound healing in vivo by increasing VEGF expression: A novel potential active ingredient for pharmaceuticals - Araújo, Edilane Rodrigues Dantas; Xavier-Santos, Jacinthia Beatriz; da Silva, Valéria Costa; de Lima, Juliana Bessa Figueiredo; Schlamb, Jade; Fernandes-Pedrosa, Matheus de Freitas; da Silva Júnior, Arnóbio Antônio; de Araújo Júnior, Raimundo Fernandes; Rathinasabapathy, Thirumurugan; Moncada, Marvin; Esposito, Debora; Guerra, Gerlane Coelho Bernardo; et al. (Frontiers in Pharmacology, 2023)
Bryophyllum pinnatum (Crassulaceae) is used in traditional medicine for treating skin wounds. In our previous study a topical gel containing B. pinnatum aqueous leaf extract showed preclinical anti-inflammatory effect in in vivo acute edema models. In continuation, the present study was aimed to evaluate the phytochemical content and the stability of a formulation in gel containing B. pinnatum aqueous leaf extract and its healing properties and mechanism of action through an experimental model of induction of skin wounds in rats and in vitro assays. The animals were treated topically for 7 or 14 days with a formulation in gel containing extract at 5% or a placebo or Fibrinase® in cream. In addition, to establish some quality control parameters the total phenolic (TPC) and flavonoid (TFC) content and a stability study focusing on phytochemical and biological stability and of a gel was carried out. Gel formulation containing extract showed a TPC and TFC of 2.77 ± 0.06 mg of gallic acid/g and 1.58 ± 0.03 mg of quercetin/g, respectively. Regarding the stability study, formulation in gel showed no significant change in pH, water activity, chromatographic profile of extract and in the content of major compound identified in extract on 30 days at two different conditions, room temperature and 40 ºC/75% RH. The gel formulation containing extract stimulated the healing of skin wounds, with a reduction in the wound area, besides that decrease the inflammatory infiltrate, reduced the levels of IL-1β and TNF-α, and stimulation of angiogenesis with increased expression of VEGF, in a similar effect of Fibrinase. In conclusion, the gel formulation containing extract exhibited relevant skin wound healing properties and therefore has potential to be applied as a novel active ingredient for developing wound healing pharmaceuticals.